2015
DOI: 10.1016/j.biopsych.2015.01.014
|View full text |Cite
|
Sign up to set email alerts
|

The Novel Metabotropic Glutamate Receptor 2 Positive Allosteric Modulator, AZD8529, Decreases Nicotine Self-Administration and Relapse in Squirrel Monkeys

Abstract: Background Based on rodent studies, Group II metabotropic glutamate receptors (mGluR2 & 3) were suggested as targets for addiction treatment. However, LY379268 and other Group II agonists do not discriminate between the mainly presynaptic inhibitory mGluR2 (the proposed treatment target) and mGluR3. These agonists also produce tolerance over repeated administration and are no longer considered for addiction treatment. Here, we determined the effects of AZD8529, a selective positive allosteric modulator (PAM) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 47 publications
3
47
0
Order By: Relevance
“…It was recently shown that AZD8529 decreases nicotine self-administration as well as nicotineprimed and cue-induced reinstatement of nicotine seeking in squirrel monkeys (Justinova et al, 2015). Moreover, AZD8529 reduces cue-induced methamphetamine craving in rats in both models of voluntary and forced abstinence from the drug (Caprioli et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was recently shown that AZD8529 decreases nicotine self-administration as well as nicotineprimed and cue-induced reinstatement of nicotine seeking in squirrel monkeys (Justinova et al, 2015). Moreover, AZD8529 reduces cue-induced methamphetamine craving in rats in both models of voluntary and forced abstinence from the drug (Caprioli et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…AZD8529 is a new, highly specific PAM that potentiates the effect of glutamate on the mGluR2 with little effect on other mGluR subtypes (Cross, 2013;Justinova et al, 2015). It has recently been shown that AZD8529 decreases nicotine self-administration, nicotine-primed, and cueinduced reinstatement of nicotine seeking in squirrel monkeys (Justinova et al, 2015), as well as incubation of methamphetamine craving in rats (Caprioli et al, 2015). Its effects on self-administration or relapse to other classes of addictive substances are presently unknown.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Systemic administration of this compound decreases cued nicotine intake and cue-and nicotineinduced seeking (Justinova et al, 2015) as well as cueinduced methamphetamine seeking (Caprioli et al, 2015). Interestingly, AZD8529 was effective at inhibiting cued nicotine seeking at doses that did not affect food seeking, indicating that the selective activation of mGluR2 may prove a more effective treatment of relapse given the lack of a negative effect on natural rewards.…”
Section: Group II Metabotropic Glutamate Receptors (Metabotropic Gmentioning
confidence: 99%
“…For these reasons, focus has shifted to selective positive allosteric modulators (PAMs) of mGlu2 receptors. Recent studies show that systemic administration of a PAM of mGlu2 receptors reduces nicotine- and cue-induced reinstatement of nicotine-seeking behavior, and that these effects are associated with reduced dopamine release in the NAc [94, 95]. Based on these studies, a phase II clinical trial examining the efficacy of the mGlu2 receptor PAM AZD8529 in human smokers is currently underway [96], with preliminary results forthcoming.…”
Section: Neurotransmitter Mechanisms Regulating Nicotine Seekingmentioning
confidence: 99%